2014
DOI: 10.1108/lodj-07-2012-0082
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and depressive symptoms among employees: mediating factors

Abstract: Transformational leadership and depressive symptoms among employees: Mediating factors Research paper AbstractPurpose. The study aims to examine whether the link between transformational leadership and depressive symptoms among employees is mediated by such personal resources as occupational self-efficacy, perceived meaningfulness of the work, and work-related rumination.Design/methodology/approach. The study was conducted using questionnaires among 557

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 86 publications
5
57
1
2
Order By: Relevance
“…As reported previously (Perko et al, 2014), there were slightly more women among the respondents at T1 as compared to the population in the work units (85% vs. 81%). Respondents who continued participation at T2 (n = 262) did not differ from those who discontinued participation (n = 292) at T2 with respect to their ratings in any of the study variables at T1, or in gender or age (Perko, Kinnunen, Tolvanen, & Feldt, 2016).…”
Section: Attrition Analysessupporting
confidence: 62%
See 1 more Smart Citation
“…As reported previously (Perko et al, 2014), there were slightly more women among the respondents at T1 as compared to the population in the work units (85% vs. 81%). Respondents who continued participation at T2 (n = 262) did not differ from those who discontinued participation (n = 292) at T2 with respect to their ratings in any of the study variables at T1, or in gender or age (Perko, Kinnunen, Tolvanen, & Feldt, 2016).…”
Section: Attrition Analysessupporting
confidence: 62%
“…These time lags were mainly determined based on the schedule of an intervention that was conducted in other countries participating in the project. The response rate at baseline was 62.5% (for details of the T1 sample and participant recruitment, see Perko et al, 2014). Of the T1 participants, 47.2% continued participation at T2.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Transformational leadership consists of four sub-dimensions: (1) idealized influence, in which the leaders are admired, respected, and trusted; (2) inspirational motivation, which reflects how leaders motivate and inspire employees by providing meaning and challenge in their work; (3) intellectual stimulation, which refers to stimulating employees' efforts to be innovative and creative by questioning assumptions, reframing problems, and approaching old situations in new ways; and (4) individualized consideration, which involves leaders paying more attention to each individual follower's needs for achievement and growth by acting as a coach or mentor (Bass 1985;Bass and Riggio 2006). Previous studies have consistently suggested that transformational leadership is related to followers' positive attitudes and performances (e.g., Perko et al 2014;Chan and Mak 2014).…”
Section: Transformational Leadership and Employee Voicementioning
confidence: 94%
“…The participants in the present cross-sectional study were public sector workers employed by four municipalities in Finland (N = 333). The data utilized in this study were collected in the late spring of 2012 at the second wave of longitudinal data collection in the larger project (see Perko, Kinnunen and Feldt, 2014;Perko, Kinnunen, Tolvanen and Feldt, 2016). Of the 333 participants in the second wave (T2), 262 had also participated in the first wave (T1) in the spring of 2011.…”
Section: Participants and Proceduresmentioning
confidence: 99%